2009
DOI: 10.1177/1934578x0900400506
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and the Role of Citrus Juices as Functional Food

Abstract: The literature on the content and stability of vitamin C (ascorbic acid, AA) in citrus juices in relation to industrial practices is reviewed. The role of vitamin C from citrus juices in human diet is also reviewed. Citrus fruits and juices are rich in several types of bioactive compounds. Their antioxidant activity and related benefits derive not only from vitamin C but also from other phytochemicals, mainly flavonoids. During juice processing, temperature and oxygen are the main factors responsible for vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 263 publications
(297 reference statements)
10
75
0
3
Order By: Relevance
“…Carotenoids are also found in the abundance in citrus fruits, with over 115 of them that have been identified 21. Numerous studies have demonstrated that high carotenoid intake may decrease the risk of cardiovascular disease, age‐related macular degeneration, and cancer 22. Among the carotenoids, β‐carotene, lutein, zeaxanthin, β‐cryptoxanthin, and lycopene are found to be the most in citrus fruits 19.…”
Section: Pancreatic Cancer and Whole Foodsmentioning
confidence: 99%
“…Carotenoids are also found in the abundance in citrus fruits, with over 115 of them that have been identified 21. Numerous studies have demonstrated that high carotenoid intake may decrease the risk of cardiovascular disease, age‐related macular degeneration, and cancer 22. Among the carotenoids, β‐carotene, lutein, zeaxanthin, β‐cryptoxanthin, and lycopene are found to be the most in citrus fruits 19.…”
Section: Pancreatic Cancer and Whole Foodsmentioning
confidence: 99%
“…Citrus fruit and related products are rich in ASC (Nagy, 1980). They are widely consumed as a functional food in the world and provide an important source of ASC for human health (Martí et al, 2009). The ASC content in citrus fruit juice sacs is 20-100 mg per 100 mL juice, which varies greatly depending on species or variety (Nagy, 1980;Lee and Kader, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The authors have been reported a first‐order kinetics for vitamin C degradation and corresponding activation energy ranging between 12 and 25 kcal ⋅ mol −1 . The initial concentration of dissolved oxygen has a major impact on vitamin C degradation to dehydroascorbic acid and 2,3‐diketogulonic acid . The UV irradiation of fruits and vegetables, before and after harvest may be considered an efficient method for enhancing the content of antioxidant compounds .…”
Section: Introductionmentioning
confidence: 99%